Higher Education and a Cosmopolitanism of Illusions - Davids, N (South African Journal of Higher Education, 2016)
When Mohamed Bouazizi, a Tunisian university graduate, set himself on fire to protest his loss of livelihood and the humiliation he suffered when the government confiscated his fruit and vegetable stand – a situation that sparked the subsequent Tunisian revolution on 17 December 2010 – the purpose of higher education again came under the spotlight. The kind of dystopia experienced through the subsequent Arab uprisings in many northern African countries foregrounds what higher education institutions on the African continent are supposed to do in order to deal with the political and ethnic violence we are witnessing on a daily basis. In this article we argue, firstly, that higher education cannot turn a blind eye to the perpetual violence in several African communities and, secondly, that higher education institutions should take more seriously the call for a ‘cosmopolitanism without illusions’ – one that can engender moments of democratic iterations, the recognition of human rights, and the restoration of human dignity.